Studi Kasus Putusan Mahkamah Agung No. 300K/PDT/2010 dan Keterkaitannya dengan Konsepsi Strategic Lawsuit Against Public Participation (SLAPP) dalam Perspektif Hukum Perlindungan Konsumen - Adrasitta Khaliddya Fithrianni; Aam Suryamah; Agus Suwandono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Prita Mulyasari case in 2008 highlighted the challenges of protecting consumers from strategic lawsuit against public participation (SLAPP) suits. SLAPPs aim to stop and prevent individuals or non-governmental organisations from exercising their right to voice their opinions publicly. However, specific regulations addressing SLAPP in the realm of consumer protection in Indonesia are still lacking. The Prita Mulyasari case underscores the need for further attention to establish clear and specific rules to protect consumers from SLAPP practices. This research will further examine how the Supreme Court Decision No. 300K/PDT/2010 in the Prita Mulyasari case can serve as a benchmark in upholding consumer rights within the Indonesian legal framework, especially given the absence of a legal umbrella that protects consumers from lawsuits aimed at limiting public participation in the form of SLAPPs by businesses. This research will employ a normative juridical approach, focusing on primary, secondary, and tertiary legal materials. The study will analyze data gathered from literature reviews using a qualitative normative data analysis method. The research findings indicate that although the Supreme Court granted Prita Mulyasari’s appeal, the legal reasoning in Decision No. 300K/PDT/2010 did not explicitly address the concept of SLAPP. The Supreme Court’s considerations largely focused on the fulfilment of the elements of tort under Article 1365 of the Civil Code. However, the Supreme Court’s use of Article 28F of the 1945 Constitution to justify Prita Mulyasari's conduct is a crucial step in strengthening the legal position of those who express criticism or complaints, as well as their status as consumers.